KEEFEKTIFAN MODEL PEMBELAJARAN INQUIRY BASED LEARNING UNTUK MENINGKATKAN SELF DIRECTED LEARNING MAHASISWA - Setyawati, Sri Panca (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTIt is necessary developing the student self directed, because it is one of education aims in Indonesia. It ought to be develop in the college such as the university. In fact, some lecturers have not done yet their task to develop their students’ self directed optimally and professionally. This condition was showed by their application of teaching method which is characterized by one way information concept and it will make the students are passive. It is necessary to apply the teaching method that will develop the students’ self directed learning such as the Inquiry Based Learning Model. The purpose of this study was to examine the effects of inquiry based learning on self directed learning. The study was a quasi experiment with the pretest-posttest control group. The result showed: the inquiry based learning was effective to promote the students’ self directed learning.Key Words: Inquiry based learning, Self directed learning.